2015
DOI: 10.1007/s10967-015-4249-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on the gamma-ray irradiation behavior of mesoporous silica adsorbents functionalized with phosphine oxide and phosphonic acid ligands

Abstract: The resistance of mesoporous silica adsorbents bearing phosphine oxide (SBA-P(O)Pr 2 ) and phosphonic acid (SBA-P(O)(OH) 2 ) to gamma-ray irradiation (in air and 2 mol/ L HNO 3 solution) was systematically evaluated. The change in the composition, structure and (U(VI)) adsorption ability of the adsorbents was examined. Both the organophosphorus ligands functionalized adsorbents exhibited remarkable durability under gamma-ray irradiation up to a total dose of 5 9 10 5 Gy. The mesoporous silica framework and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…To date, a variety of sorbents have been developed for exaction of uranium from highly acidic and/or radioactive medium, such as synthetic resins, mesoporous silica and covalent organic framework . For example, Subramanian et al .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of sorbents have been developed for exaction of uranium from highly acidic and/or radioactive medium, such as synthetic resins, mesoporous silica and covalent organic framework . For example, Subramanian et al .…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports of the inorganic particle's synthesis, such as silica, using gamma irradiation [25,26]. Zhan et al introduced gamma ray during the process synthesis of mesoporous silica, and they successfully obtained well-kept Si particles [27].…”
Section: Scheme 1 Synthesis Of Hybrid Crosslinked Films By Gamma Radi...mentioning
confidence: 99%
“…To date, irradiation of mesoporous SBA-15 silica grafted with various ligands has been studied using gamma irradiation [23,[27][28]. However, the dose accumulated in these studies was quite low (from 10 kGy to 500 kGy).…”
Section: Introductionmentioning
confidence: 99%
“…However, the dose accumulated in these studies was quite low (from 10 kGy to 500 kGy). Zhang et al [28] showed that phosphine oxide and phosphinic acid ligands grafted on a SBA-15 matrix retain their sorption ability when irradiated up to 500 kGy. Iqbal et al [23,27] evidenced no or little reduction of the sorption ability of ethylenediaminetetraacetic acid, aminopropyl and N-propylsalicyl-aldimino grafted SBA-15 irradiated up to 1 kGy.…”
Section: Introductionmentioning
confidence: 99%